2023
DOI: 10.1111/jora.12895
|View full text |Cite
|
Sign up to set email alerts
|

Justice for me and for all: Longitudinal analysis of justice perceptions across demographic indicators

Kendra J. Thomas,
Herbert Rodrigues,
André V. Komatsu

Abstract: Most research on justice perceptions stems from high‐income contexts, even though most youth grow up in contexts of inequality and injustice. This study examines the development of justice perceptions in 659 Brazilian adolescents (51.3% male; 45.2% White) in São Paulo across 3 years, ages 12, 13, and 14. Perceptions of justice of the world declined with age and perceived justice in one's personal life differed across ethnic, economic, and educational groups. Privileged groups differentiated more between their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Studies reported in the articles examine aspects of emotional (Shi et al, 2024), cognitive (Lichand et al, 2024;Thomas et al, 2024), and moral development (Pandya & Bhangaokar, 2024;Nwafor et al, 2024), prosocial behavior (Mesurado & Resett, 2024), adolescents' use of time (Kerai et al, 2024), their perceptions of work (Santana & Ristum, 2024), social identity processes (Appachu & F I G U R E 1 Timeline and decision-making process for the Special Issue. Singh, 2024), health (e.g., body image, Mahama et al, 2024), and well-being (Zambrano et al, 2024).…”
Section: Ov Erv Iew Of Th E Speci a L Is Su E A Rticl E Smentioning
confidence: 99%
See 2 more Smart Citations
“…Studies reported in the articles examine aspects of emotional (Shi et al, 2024), cognitive (Lichand et al, 2024;Thomas et al, 2024), and moral development (Pandya & Bhangaokar, 2024;Nwafor et al, 2024), prosocial behavior (Mesurado & Resett, 2024), adolescents' use of time (Kerai et al, 2024), their perceptions of work (Santana & Ristum, 2024), social identity processes (Appachu & F I G U R E 1 Timeline and decision-making process for the Special Issue. Singh, 2024), health (e.g., body image, Mahama et al, 2024), and well-being (Zambrano et al, 2024).…”
Section: Ov Erv Iew Of Th E Speci a L Is Su E A Rticl E Smentioning
confidence: 99%
“…Studies also investigate family processes including family obligation (Yang et al, 2024), role of family in adolescents' occupational choices (Pease Dreibelbis et al, 2024), grandparenting (Tan et al, 2024), and parental socialization of adolescent emotions (Shi et al, 2024). Methodologically, studies utilize a variety of qualitative approaches (Appachu & Singh, 2024;Kerai et al, 2024;Pandya & Bhangaokar, 2024;Pease Dreibelbis et al, 2024;Santana & Ristum, 2024;Zambrano et al, 2024), mixed-methods approaches (Tan et al, 2024;Mahama et al, 2024;Shaikh & Sarin, 2024), prospective longitudinal designs (Pandya & Bhangaokar, 2024;Shi et al, 2024;Thomas et al, 2024), quantitative studies with variablecentered approaches to data analysis (Shi et al, 2024;Nwafor et al, 2024) as well as person-centered approaches (Thomas et al, 2024;Zhao et al, 2024). This methodological pluralism highlights the relevance of different approaches with various adolescent communities in the Majority World.…”
Section: Ov Erv Iew Of Th E Speci a L Is Su E A Rticl E Smentioning
confidence: 99%
See 1 more Smart Citation